Aux sources de la sémiologie graphique - Gilles Palsky; Marie-Claire Robic (Cybergeo, 2000)
Graphical semiotics is an innovation connected with the itinerary of a person gifted with a real genius of the visual. It has spread out through fundamental experiences in research and through the need for territorial statistics in the 60’s. From the 50’s on, Bertin developed studies which contrast with his classical education to map-making, and leads to Sémiologie graphique. The treatise was published in a context of expansion of semiotics, particularly visual one. It summarizes some rules stemming practical experience and emphazises sight as a tool for data processing and portraying.